2017
DOI: 10.1093/jnci/djx029
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Trial Comparing a Web-Mediated Follow-up With Routine Surveillance in Lung Cancer Patients

Abstract: A web-mediated follow-up algorithm based on self-reported symptoms improved OS due to early relapse detection and better performance status at relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
390
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(405 citation statements)
references
References 20 publications
5
390
0
10
Order By: Relevance
“…Actively retrieving patients' concerns increased survival and quality of life in a randomized trial on lung cancer, because clinicians often fail to reliably detect and address patients' symptoms and underestimate their severity . Inclusion of patient‐reported outcomes improved understanding of patient's experience, symptom management, and outcomes .…”
Section: Quality Measures For Sdmmentioning
confidence: 99%
“…Actively retrieving patients' concerns increased survival and quality of life in a randomized trial on lung cancer, because clinicians often fail to reliably detect and address patients' symptoms and underestimate their severity . Inclusion of patient‐reported outcomes improved understanding of patient's experience, symptom management, and outcomes .…”
Section: Quality Measures For Sdmmentioning
confidence: 99%
“…Research evidence for significant benefits for using patient‐reported outcome measures (PROMs) data in direct individual patient care is accumulating (Basch, ; Denis et al, ). Some clinicians appear to be interested in using PROMs in routine clinical practice as it captures patients’ experiences of treatment and disease in a systematic way, using valid and reliable measures.…”
Section: Introductionmentioning
confidence: 99%
“…Denis et al [6, 7] concentrated on advanced-stage lung cancer patients without evidence of disease progression after or during the initial treatment. Patients were randomly assigned in a multicenter phase III trial to compare a web-mediated follow-up algorithm (experimental arm), based on weekly self-scored patient symptoms with routine follow-up with CT scans scheduled every 3–6 months according to the disease stage (control arm).…”
Section: Ehealth In Therapy Managementmentioning
confidence: 99%
“…The median overall survival was 22.5 months in the intervention group versus 14.9 months in the control group, without censoring for crossover (hazard ratio, 0.59 [95% CI, 0.37–0.96]; p = 0.03). Denis et al [6, 7] used MoovCare from Sivan Innovation, which is a medical device [8]. …”
Section: Ehealth In Therapy Managementmentioning
confidence: 99%